1997
DOI: 10.1128/mcb.17.3.1615
|View full text |Cite
|
Sign up to set email alerts
|

DAP-5, a Novel Homolog of Eukaryotic Translation Initiation Factor 4G Isolated as a Putative Modulator of Gamma Interferon-Induced Programmed Cell Death

Abstract: A functional approach to gene cloning was applied to HeLa cells in an attempt to isolate cDNA fragments which convey resistance to gamma interferon (IFN-␥)-induced programmed cell death. One of the rescued cDNAs, described in this work, was a fragment of a novel gene, named DAP-5. Analysis of a DAP-5 full-length cDNA clone revealed that it codes for a 97-kDa protein that is highly homologous to eukaryotic translation initiation factor 4G (eIF4G, also known as p220). According to its deduced amino acid sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
127
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 132 publications
(131 citation statements)
references
References 55 publications
3
127
1
Order By: Relevance
“…Over-expression of the factor has been reported to cause malignant transformation (Fukuchi-Shimogori et al, 1997). Intriguingly, a fragment of a gene that encodes a mammalian homologue of the C-terminal part of eIF4G, variously called p97, DAP-5 or NAT1 Levy-Strumpf et al, 1997;Yamanaka et al, 1997), has been reported to protect HeLa cells against interferong-induced apoptosis. The functional relationship, if any, of p97/DAP-5/NAT1 to the ca.…”
Section: Discussionmentioning
confidence: 99%
“…Over-expression of the factor has been reported to cause malignant transformation (Fukuchi-Shimogori et al, 1997). Intriguingly, a fragment of a gene that encodes a mammalian homologue of the C-terminal part of eIF4G, variously called p97, DAP-5 or NAT1 Levy-Strumpf et al, 1997;Yamanaka et al, 1997), has been reported to protect HeLa cells against interferong-induced apoptosis. The functional relationship, if any, of p97/DAP-5/NAT1 to the ca.…”
Section: Discussionmentioning
confidence: 99%
“…DAP5/ p97/NAT1) stem from the fact that the gene was identified and cloned simultaneously by four independent groups. [60][61][62][63] In our laboratory, DAP5 was isolated as a positive mediator of IFN-g-induced cell death. 64 It was rescued in a genetic screen, which was based on knocking down RNA expression by transfection with antisense cDNA libraries followed by positive growth selection.…”
Section: Dap5/p97/nat1 -The Discovery Of the Gene And Initial Structumentioning
confidence: 99%
“…Independently, expression of an antisense cDNA fragment of DAP5 was also found to exert similar death-protective effects, further establishing the role of DAP5 as a positive mediator of cell death in the IFN-g system, which represents a slow type of cell death. 61 In parallel, Sonenberg and colleagues cloned DAP5/p97 in an effort to identify novel homologs of the eukaryotic translation initiation factor eIF4GI. 60 In addition, Shaughnessy et al, cloned the mouse DAP5 gene based on its physical linkage to a common retroviral integration site found in myeloid leukemia of BXH2 mice.…”
Section: Dap5/p97/nat1 -The Discovery Of the Gene And Initial Structumentioning
confidence: 99%
See 2 more Smart Citations